2014
DOI: 10.1007/s11248-014-9845-5
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 Pr55gag polyprotein binds to plastidial membranes and leads to severe impairment of chloroplast biogenesis and seedling lethality in transplastomic tobacco plants

Abstract: Chloroplast genetic engineering has long been recognised as a powerful technology to produce recombinant proteins. To date, however, little attention has been given to the causes of pleiotropic effects reported, in some cases, as consequence of the expression of foreign proteins in transgenic plastids. In this study, we investigated the phenotypic alterations observed in transplastomic tobacco plants accumulating the Pr55(gag) polyprotein of human immunodeficiency virus (HIV-1). The expression of Pr55(gag) at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…In particular, they showed chloroplasts with irregular shape and a severely defective ultrastructure characterized by rudimentary and unstacked internal membranes dispersed in an electron-dense matrix, resembling to proplastids. Similar results were also observed in our laboratory for tobacco transplastomic plants expressing HIV-1/Pr55 gag [ 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…In particular, they showed chloroplasts with irregular shape and a severely defective ultrastructure characterized by rudimentary and unstacked internal membranes dispersed in an electron-dense matrix, resembling to proplastids. Similar results were also observed in our laboratory for tobacco transplastomic plants expressing HIV-1/Pr55 gag [ 52 ].…”
Section: Discussionsupporting
confidence: 89%
“…Pigments content was spectrophotometrically determined at 665, 649 and 470 nm using a Perkin Elmer Lambda25 UV/VIS spectrometer. Calculations were based on formulas described elsewhere [ 32 ]. Three biological and three technical replicates were used to evaluate each experimental condition.…”
Section: Methodsmentioning
confidence: 99%
“…So far, only the expression of a dengue virus serotype 3 premembrane and envelope polyprotein has been reported in plastids (Kanagaraj et al 2011). We demonstrate that dengue virus envelop protein domain III-based antigens can be expressed in tobacco chloroplasts and that the expression of challenging proteins via the ethanol-inducible expression system offers a possibility to avoid deleterious phenotypes associated with overexpression (Hennig et al 2007;Petersen and Bock 2011;Scotti et al 2015). The transplastomic plant lines with the transgene expression cassette controlled by the strong constitutive ribosomal RNA operon promoter showed distinct growth retardations and mild pigment deficiency.…”
Section: Discussionmentioning
confidence: 84%
“…The transplastomic plant lines with the transgene expression cassette controlled by the strong constitutive ribosomal RNA operon promoter showed distinct growth retardations and mild pigment deficiency. In many cases, plastid expression of recombinant proteins does not result in abnormal phenotypes, but an increasing number of studies has reported phenotypic alterations in transplastomic plants (Lössl et al 2003;Magee et al 2004;Scotti et al 2015;Tissot et al 2008;Tregoning et al 2003;Waheed et al 2011). The two main reasons underlying pigment deficiency or a delay in plant development are toxicity of the transgene product due to interference of the recombinant protein with essential processes in the chloroplast (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation